Shahrbānū's Recompense: Muslim and Non-Muslim Antagonists and the Hero-Imam in Rabīʿ’s Alī nāma - Warner, George (Entangled Religions, 2023)
This article explores the central antagonisms at work within the Alī nāma of Rabīʿ, a fifth/eleventh-century Persian epic by a Twelver Shīʿī poet narrating the deeds of ʿAlī b. Abī Ṭālib, in particular the battles of the Camel and of Ṣiffīn. It gives an analysis of this poem within its twin contexts of Shīʿī imamology and Persian poetry, illustrating how these fields are variously drawn upon, combined and challenged in the poem’s unique narrative of the imam, and arguing that Rabīʿ cultivates his oft-cited opposition between Arabo-Islamic truth-telling and Iranian/Zoroastrian deception as a means of navigating intra-Muslim sectarian dynamics. The article argues against reductionist views of the poem, demonstrating the hybrid nuance of its engagement with Sunnīs, Shīʿīs and the pre-Islamic past, as well as providing an overview of this under-studied work of literature.